Lex Ad Astra : Non-State Actor Accountability for Space Pollution - Gillett, Matthew, (Studies in Space Law ;, 2025)
Outer space has long been considered the last untouched wilderness. However, non-State actors are increasingly active in space, heightening the risk of space pollution. Space law, designed during the Cold War, is State-centric and makes inadequate provision for non-State actors. In the face of this emerging threat, this book examines potential avenues of redress in space law, including the Outer Space Treaty, along with international environmental law, international criminal law, international humanitarian law, and international human rights law. It also reviews the national legislation adopted by space-faring States at the domestic level. In parallel, the book examines the deeper theoretical implications addressing non-State actor conduct under international law. Ultimately, it proposes a ground-breaking new international law instrument to hold non-State actors responsible for space pollution.